Feasibility of Community Information Centres and The Implications for Technological Innovations in Afikpo, Ebonyi State, Nigeria - Igwe, Kingsley Nwadiuto; Ndubuisi-Okoh, Elizabeth O.; Odenigbo, Patience (International Journal of Knowledge Content Development & Technology, 2023)
The development of rural areas is expected to be holistic covering all essential infrastructure. Community information centres (CICs) are agencies that should be part of the infrastructures for rural development. Unfortunately, these centres are hardly seen in rural communities in Nigeria, including Afikpo in Ebonyi State. Thus, this study was conceived to explore the perceptions of citizens towards the establishment of CICs in the locality. It adopted survey research method with questionnaire as instrument for data collection, which was self-developed and validated by experts with a pre-texted reliability index of 0.72. A total of 399 copies of the questionnaire were distributed, out of which 267 copies were properly completed, representing 67% and were used for analysis. Findings revealed that the citizens have overall positive perception towards establishing the CICs; they are also knowledgeable of the benefits of such centres. Furthermore, there are workable suggestions on ways of establishing, funding and managing CICs in Afikpo. In addition, about 65% of the respondents indicated interest to assist and support the funding and management of the CICs when established. However, the challenges of inadequate funding and support as well as the possible politics of where to site/locate the CICs in Afikpo, are likely impediments to the project. The study concluded that citizens have strong and positive disposition towards establishing CICs in Afikpo. The implications of such CICs for technological innovations were analysed. The study recommends, among others, that government should see the establishment of CICs as priority projects that would significantly contribute to the growth and development of rural communities in Nigeria; communities in Afikpo should explore self-help approach to development; and political representatives from Afikpo should take advantage of establishing CICs as constituency projects for the citizens.